Philo-Semitism in Nineteenth-Century German Literature - Massey, Irving (Conditio Judaica, 2000)
The work deals with philo-Semitic texts by the non-Jewish authors of the 19th century. The writer who provides the largest body of relevant material is Leopold von Sacher-Masoch, but works by Gutzkow, Bettine von Arnim, Annette von Droste-Hülshoff, Hebbel, Freytag, Raabe, Fontane, Grillparzer, Ebner-Eschenbach, Anzengruber, and Ferdinand von Saar are also examined, as are several tales by the Alsatian authors Erckmann and Chatrian. There is a short chapter on women and philo-Semitism. The conclusion draws attention to the feelings of guilt that are revealed in a number of the texts.